Investigating the effects of physical and cognitive demands on quality of performance and subjective responses under pacing/ takt time - Shaikh, Shakil Ahmed (2015)
Assembly work requires high levels of performance and quality but may involve complex cognitive and physical tasks. There is evidence that physical and cognitive workloads are not separate, but may interact. Work in exercise and simple physical tasks suggests that physical load may lead to changes in cognitive performance, and in perceived workload. The aim of this thesis is to examine physical and cognitive interactions that might affect assembly work. First, observation was undertaken in industry to identify the physical and cognitive factors relevant to examples of assembly lines. From this, a task analysis of a simulated assembly task was developed. Three experimental studies were conducted, based upon the simulated assembly task, in order to investigate three main assembly variables; working height, memory load and pacing. The first study showed that the number of completed assemblies was reduced when performed at higher pacing and while working at above shoulder height. The number of components dropped was higher when performed at above shoulder height. When the task was performed at elbow height ‘wait’ time increased as the beep time was found to be higher at elbow height than the above shoulder height, which led to increase wait time when performing the task at elbow height. Subjective measures (NASA TLX) showed that temporal demand and effort were reported as higher during high pacing. Perceived physical and temporal demand increased when working above shoulder height. An interaction on subjective measure was identified between pacing and working height. Performance of NASA TLX was found to be poor when performing the assembly operation at high pacing/Takt and above shoulder height as compared to working at high pacing/ Takt and elbow height.